Studi pengaruh suhu kondensasi R245FA, R515A, dan R1234ZE terhadap kinerja siklus Rankine organik - Marianus R. V. T. Etu; Matheus Magnus Dwinanto; Jack Carol Adolf Pah (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
The organic Rankine cycle has been used as a power plant that utilizes low temperature heat sources such as biomass, geothermal, and waste heat from conventional power plants. This study was conducted to analyze the energy performance of the organic Rankine cycle as a result of changes in condensation temperature using a more environmentally friendly working fluid as a substitute for R245FA, namely R515A and R1234ZE. The system performance is based on the variation of the condensation temperature using Genetron Properties software with the evaporation temperature being held constant. The important quantities analyzed are mass flow rate, pumping power, heat absorption, turbine pressure ratio, and thermal efficiency. The results of this study indicate that increasing the condensing temperature greatly increases the pumping power consumption but decreases the pressure ratio in the turbine, and the thermal efficiency of the system. The pumping power used to circulate R515A and R1234ZE is greater than that of circulating R245FA, but the thermal efficiency of the ORC system using R1234ZE is greater than that of R245FA and R515A.